Internalized homonegativity moderates the association between attachment avoidance and emotional intimacy among same-sex male couples - Guzmán-González, Mónica; Gómez, Fabiola; Bahamondes, Joaquín; Barrientos, Jaime; Garrido-Rojas, Lusmenia; Espinoza-Tapia, Ricardo; Casu, Giulia (Frontiers in Psychology, 2023)
The present study aimed to examine dyadic associations between attachment insecurity and emotional intimacy in same-sex male couples, and to investigate whether and how each partner’s internalized homonegativity (IH) moderated these associations The sample included 138 male same-sex couples. Both dyad members completed self-report measures of attachment insecurity, emotional intimacy, and IH. The actor-partner interdependence model with moderation analysis was applied. Results indicated that higher levels of actor’s and partner’s attachment anxiety and attachment avoidance were associated with lower actor’s emotional intimacy. IH moderated the partner effects of attachment avoidance on emotional intimacy. The partner’s higher attachment avoidance was associated with one’s own lower emotional intimacy at low (but not high) levels of one’s own IH and at high (but not low) levels of the partner’s IH. Findings suggest the partner’s attachment avoidance may differently affect one’s own emotional intimacy depending on the IH levels of both dyad members. Helping partnered sexual minority men decrease attachment insecurity while recognizing their own and their partners’ IH may promote relationship quality.